2013
DOI: 10.1002/smll.201302424
|View full text |Cite
|
Sign up to set email alerts
|

Optically Controlled Pore Formation in Self‐Sealing Giant Porphyrin Vesicles

Abstract: Efforts to develop self-contained microreactors and artificial cells have been limited by difficulty in generating membranes that can be robustly and repeatedly manipulated to load and release cargo from phospholipid compartments. Here we describe a purely optical method to form pores in a membrane generated from porphyrin-phospholipid conjugates electro-assembled into microscale giant porphyrin vesicles and manipulated using confocal microscopy. The pores in the membrane resealed within a minute allowing for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The nature of the NIR-induced permeabilization is not well understood and further work must seek to better characterize both its chemical and physical mechanism. Optical microscopy has recently been shown to be useful for observing light-induced permeabilization in porphyrin–lipid microvesicles48, although mechanistic aspects between nanoscale and microscale vesicle permeabilization are likely different. Although the in vivo results of the systemically administered Dox–PoP-liposomes clearly demonstrated the synergistic effects of light treatment, further investigation is required to characterize the mechanism of action in the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the NIR-induced permeabilization is not well understood and further work must seek to better characterize both its chemical and physical mechanism. Optical microscopy has recently been shown to be useful for observing light-induced permeabilization in porphyrin–lipid microvesicles48, although mechanistic aspects between nanoscale and microscale vesicle permeabilization are likely different. Although the in vivo results of the systemically administered Dox–PoP-liposomes clearly demonstrated the synergistic effects of light treatment, further investigation is required to characterize the mechanism of action in the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…To generate local hyperthermia to induce transient membrane rupture, it is not necessary to limit to the use of NIR light absorbing metal nanostructures. In another study, it was demonstrated that red light (658 nm, 200 mW cm −2 , 10 min) irradiation of porphyrin‐conjugated phospholipid‐based liposome (PoP‐liposome) can successfully lead to release of encapsulated doxorubicin from the liposomes . When the porphyrin lipid is beyond 10 mol% in the liposome membrane, self‐quenching of photoexcited porphyrin moieties can effectively convert photon energy to heat, leading to drastic increase in the transient membrane permeability, rapid release of encapsulated DOX anticancer drug, decrease in the in vitro cell viabilities, and prolonged average lifespan of KB tumor‐bearing nude mice .…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…However, near‐infrared phosphorescence emission at 1270 nm is the most widely used detection method. Alternatively, singlet oxygen can also be detected using the spin‐trapping ESR technique with the help of spin‐trapping agents such as 2,2,6,6‐tetramethyl‐4‐piperidone (TEMP) to form a TEMPO (TEMP‐ 1 O 2 ) spin adduct . The reaction of chemiluminescence probe reagents with 1 O 2 generates an electronically excited fluorescent product .…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Light-triggered reversible opening and sealing can also be achieved at the micro-scale. [380] Recently, Luo et al found that the light-triggered drug release speed can be controlled by adjusting the concentrations of porphyrin-phospholipid (PoP) and unsaturated lipid in the liposome, and the stability can be tuned by varying the drug-to-lipid ratio. [381, 382] With only 2% PoP in a conventional long-circulating liposome formulation, blood circulation of entrapped doxorubicin was 21.9 h, and was effective for tumor photoablation relative to photodynamic therapy or chemotherapy alone.…”
Section: Theranostic Nanomaterialsmentioning
confidence: 99%